(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The removal of impacted third molars is a common oral surgical procedure. Surgical extraction of third molars is often accompanied by pain, swelling, trismus, limited mouth opening and general oral dysfunction during the healing period[1].The first phase of wound healing starts by formation of clot and initiation of inflammation, which than progresses to proliferative stage that consist of epithelialization, neoangiogenesis, granulation tissue formation and collagen formation and finally maturation and shrinkage. Growth factors are mitogenic, chemo tactic and angiogenic. They are very crucial to the healing process of wounds[2].